2000
DOI: 10.1007/s002130000428
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety-induced antinociception in mice: effects of systemic and intra-amygdala administration of 8-OH-DPAT and midazolam

Abstract: These results with systemic and intracerebral drug infusion suggest that 5-HT(1A) receptors localised in the amygdala are not involved in the pain inhibitory processes that are "recruited" during aversive situations. However, activation of these receptors does phasically increase anxiety. Although the intrinsic antinociceptive properties of systemically administered midazolam confounded interpretation of its effects on OAIA, intra-amygdala injections of this compound suggest that benzodiazepine receptors in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
2
6

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 75 publications
6
49
2
6
Order By: Relevance
“…As previously reported (Nunes-de-Souza et al 2000), the positive-control midazolam evoked significant anxiolytic responses, but no significant differences in the time spent in open arms were observed between the FAAH (−/−) and wild-type mice. Likewise, neither the anandamide-treated FAAH (−/−) mice nor the wild-type mice treated with anandamide or URB597 exhibited significant effects in the elevated plus maze.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…As previously reported (Nunes-de-Souza et al 2000), the positive-control midazolam evoked significant anxiolytic responses, but no significant differences in the time spent in open arms were observed between the FAAH (−/−) and wild-type mice. Likewise, neither the anandamide-treated FAAH (−/−) mice nor the wild-type mice treated with anandamide or URB597 exhibited significant effects in the elevated plus maze.…”
Section: Discussionsupporting
confidence: 74%
“…route administration in a volume of 10 μl/g body weight. The desipramine (Nielsen et al 2004) and midazolam (Nunes-de-Souza et al 2000) doses were selected from those reported in the literature, whereas the doses of URB597 were based on their ability to augment anandamide's pharmacological effects (see Fig. 1).…”
Section: Drugsmentioning
confidence: 99%
“…It appears unlikely that the anxiolytic effect observed herein was an artifact due to an effect on motor activity since entries into closed arms did not change significantly (P>0.05). Absolute number of closed-arm entries is a more reliable measure for locomotion in EPM paradigm (Nunes-de-Souza et al 2000;Rao et al 2003). Since both anxiolytic and anxiogenic agents have an effect on total number of entries, its use as a measure of locomotor or general activity has been criticized (Dawson et al 1995;Rodgers and Johnson 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of 5-HT metabolites to 5-HT was significantly higher in the frontal cortex in an SIA rat model of repeated footshocks followed by tail-flick latency in noxious thermal water (Rosecrans et al, 1986). In another model of SIA involving open-arm induced antinociception in mice, administration of 5-HT(1A) receptor agonist 8-OH-DPAT produced biphasic responses as a low dose attenuated the analgesic response whereas a high dose resulted in enhancement (Nunes-de-Souza et al, 2000).…”
Section: Monoaminergic Correlates Of Siamentioning
confidence: 97%